STRATEGI MANAJERIAL DAN CAPAIAN MUTU SEKOLAH - Firman Adam; Dedy Achmad Kurniady (Jurnal Administrasi Pendidikan, 2020)
This study seeks to examine the impact of the implementation of managerial strategies undertaken by principals on the achieve-ment of principals' quality. This research using quantitative research and sample in this study amounted to 27 SMA Negeri in Bandung through panel data regression analysis during the 2016-2018 period. The results showed that managerial strategy signi-ficantly influenced the achievement of school quality. Managerial strategies in this study are measured into three strategies: 1) the effectiveness of school management, 2) strengthening the competence of graduates, 3) empowering teachers and staff. The effectiveness of school management strategies has a significantly positive effect on school quality outcomes, strategy of strengthen-ing the competencies of graduates and empowering teachers and staff has no significant effect on the achievement of school quality during the 2016-2018 period. As a recommendation, school prin-cipals should encourage graduate competencies through empo-wering teachers and staff to be actively involved so that school quality can be achieved.